HUBUNGAN SOSIAL EKONOMI DAN KARAKTERISTIK AKSEPTOR KB DENGAN TINGKAT KEMANDIRIAN PESERTA KB BARU DI KELURAHAN SUNGGAL KECAMATAN MEDAN SUNGGAL KOTA MEDAN TAHUN 2012 - sry simanjuntak (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
The government in this case National Family Planning Coordination Comission introduces a new program called the Movement of Family Planning Independent. The level independence of Family Planning is a condition or mental attitude of the community in implementing Family Planning who can stand alone and did not depend on the parties/others and awake to meet their needs in Family Planning independently. This research aims to analyze relations of social economic (education, occupation, income) and characteristics of Family Planning acceptors (age, number of live child) and a level of independence New Family Planning participants in the use of Familiy Planning Independent programs (in Sunggal Sub urban, Medan Sub-district, Medan City in 2012). This research is descriptive-analytic. Population is New Family Planning acceptors, amount of 122 person and all population become samples. The data is analyzed by Chi Square test with α 0.05. The results of research indicates that the acceptors of Family Planning Independent more in Higher Education Level, who has work, income level ≥ Rp. 1.285.000.00, age of adult, and the number of life child ≤ 2 child. It indicates that factors related to the level of independence of New Family Planning acceptors are education (p<0,0001), occupation (p=0,013), income (p<0,0001), age (p<0,0001), number of life child (p=0,005). It sugestion that National Family Planning Coordination Comission do the socialization of Family Planning Independent to them who have the lower educational level, unemployee, the lower income, the younger age, and them who have more child to achieve the objective of Family Planning Independent. Keywords: Level of Independence, Social-Economics, Acceptors of New Family Planning, Characteristic of Acceptors of Family Planning